A new generation of electrospun fibers containing bioactive glass particles for wound healing - Sergi, Rachele; Cannillo, Valeria; Boccaccini, Aldo R.; Liverani, Liliana (Materials, 2020)
Chitosan fibers blended with polyethylene oxide (CHIT_PEO) and crosslinked with genipin were fabricated by electrospinning technique. Subsequently, CHIT_PEO bioactive glass composite electrospun mats were fabricated with the aim to achieve flexible structures with adequate mechanical properties and improved biological performance respect to CHIT_PEO fibers, for potential applications in wound healing. Three different compositions of bioactive glasses (BG) were selected and investigated: 45S5 BG, a Sr and Mg containing bioactive glass (BGMS10) and a Zn-containing bioactive glass (BGMS_2Zn). Particulate BGs (particles size < 20 µm) were separately added to the starting CHIT_PEO solution before electrospinning. The two recently developed bioactive glasses (BGMS10 and BGMS_2Zn) showed very promising biological properties in terms of bioactivity and cellular viability; thus, such compositions were added for the first time to CHIT_PEO solution to fabricate composite electrospun mats. The incorporation of bioactive glass particles and their distribution into CHIT_PEO fibers were assessed by SEM and FTIR analyses. Furthermore, CHIT_PEO composite electrospun mats showed improved mechanical properties in terms of Young’s Modulus compared to neat CHIT_PEO fibers; on the contrary, the values of tensile strain at break (%) were comparable. Biological performance in terms of cellular viability was investigated by means of WST-8 assay and CHIT_PEO composite electrospun mats showed cytocompatibility and the desired cellular viability.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Bioactive glasses; Chitosan; Composite fibers; Electrospinning; Mechanical properties; Wound healing